Diagnozowanie i usprawnianie funkcji oddechowej w postępowaniu logopedycznym. Ujęcie teoretyczne i praktyczne - Gacka, Ewa; Kaźmierczak, Monika (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The article is devoted to diagnosing and streamlining the respiratory function in speech-therapy proceedings. A respiration is one of primal activities with regard to the speech, and its evaluation constitutes the integral part of the speech-therapy examination. The correct way of the respiration is an essential condition of the appropriate vocal emission, of saying. In the article the ways of the diagnosis and therapy of the respiratory function (of its different aspects) applied by the speech therapists were presented both at children as well as at adult patients.